Using foresight to prepare animal health today for tomorrow’s challenges - Willis, Norman G. (Canadian Veterinary Medical Association, 2011)
Foresight has been introduced in Canada in the area of animal health as a process to broaden thinking about the future and inform policy development. Its initial use and evolution through projects and studies over the past decade are described, demonstrating real action in animal health. Despite positive, continuing, and exciting results in animal health policy development, foresight’s widespread acceptance and use thus far have been limited. Critical components for success, drawn from the Canadian experience, are described, and recommendations are offered for further action in animal health.